Feasibility of establishing a core set of sexual, reproductive, maternal, newborn, child, and adolescent health indicators in humanitarian settings: results from a multi-methods assessment in the Democratic Republic of Congo - Jacques Emina; Rinelle Etinkum; Anya Aissaoui; Cady Nyombe Gbomosa; Kaeshan Elamurugan; Kanya Lakshmi Rajendra; Ieman Mona El Mowafi; Loulou Kobeissi (BMC, 2022)
Plain Language Summary In humanitarian settings, data collection is often unreliable and not standardized-especially with regards to sexual, reproductive, maternal, newborn, child, and adolescent health (SRMNCAH). In order to address this gap in data quality, the World Health Organization proposed a list of core indicators to four countries, including the Democratic Republic of Congo (DRC). The goal was to use the findings from the DRC context to contribute to the determination of a core set of indicators. This study had two components: a feasibility assessment and a multi-methods assessment. The feasibility assessment in the DRC focused on the relevance of the proposed indicators, the feasibility of measurement, the resources in place, and ethical issues. The multi-methods assessment included a desk review, interviews with key informants, and focus groups and facility assessments. The findings showed that partners in the DRC supported developing a standard set of SRMCAH indicators that can be used among all humanitarian partners in the country. There are many systems in place that could be used or strengthened to improve data collection. However, the findings also showed that there must be better collaboration and coordination between the different partners in the DRC, as well as increased resources, to alleviate burden on frontline staff. In conclusion, though there is a desire to harmonize indicators, more input and resources are needed from the international community to aid in the standardization of data collection in order to meet local reporting requirements and ease burden on local staff.